Elucidating the mechanisms of post-stroke motor recovery mediated by electroacupuncture using diffusion tensor tractography - Kim, Min Su; Moon, Byung Soon; Ahn, Jae-yoon; Shim, Sang-song; Yun, Jong-Min; Joo, Min Cheol (Frontiers in Neurology, 2022)
Acupuncture has been commonly used for post-stroke patients, and electroacupuncture allows simultaneous application of acupuncture and electrical stimulation. We aimed to elucidate the mechanism of electroacupuncture on post-stroke motor recovery using diffusion tensor tractography. A total of 33 subacute stroke patients were recruited. The control group was subjected to conventional rehabilitation therapy. In contrast, the patients in the experimental group received electroacupuncture treatment for 30 min per session for 4 weeks in addition to the rehabilitation therapy. Fugl-Meyer assessment of the lower extremity (FMA_L), functional ambulation categories (FAC), and the Korean version of modified Barthel index (K-MBI) were used to compare behavioral outcomes between groups. The corticospinal tract (CST) was examined before and after the intervention via diffusion tensor tractography (DTT) to determine the motor recovery mechanism mediated by electroacupuncture. After 4 weeks of intervention, both the control and experimental groups showed a significant improvement with respect to FMA_L, FAC, and K-MBI. The level of improvement in FMA_L, FAC, and K-MBI did not vary significantly between the two groups. However, DTT results showed that the CST fractional anisotropy of the affected side (control: from 0.456 to 0.464, experimental: from 0.459 to 0.512) and its ratio (control: from 89.8 to 90.3, experimental: from 90.2 to 93.3) were significantly different between the two groups (p = 0.032 and p = 0.018). In addition, there were significant differences in the CST axial diffusivity of affected side (control: from 0.783 to 0.877, experimental: from 0.840 to 0.897) and its ratio variation (control: from 87.9 to 100.0, experimental: from 95.7 to 100.7) between the groups (p = 0.003 and p = 0.001). Electroacupuncture played a role in promoting brain plasticity and delaying neural degeneration in subacute period after stroke. Thus, electroacupuncture could be an effective adjuvant therapy in addition to conventional rehabilitation for motor recovery after stroke in a long-term perspective.